Ethics and social responsibility in business - Trikojus, Tom; Rowe, Claudia; McAuliffe, Mark; Video Education Australasia; Films For The Humanities & Sciences (Firm) (Princeton, NJ. : Films for the Humanities & Sciences, 2004)
'Many businesses abide by a code of conduct, either company-specific or industry-wide. This timely program distinguishes between ethical behavior and social responsibility by spotlighting two well-known Australian businesses that exhibit both qualities: Bendigo Bank and its Community Bank initiative, a cooperatively spirited venture that teaches solid commercial principles to franchisees, and The Body Shop, a skincare product provider that calls itself an activist organization committed to positive social and environmental change and a retailer committed to customer service excellence. The underlying message? Good community is good business
Keywords: Business ethics -- Australasia; Corporate culture -- Australasia; Social responsibility of business -- Australasia